Association of Hepatic Steatosis With Major Adverse Cardiovascular Events, Independent of Coronary Artery Disease - Meyersohn, Nandini M.; Mayrhofer, Thomas; Corey, Kathleen E.; Bittner, Daniel O.; Staziaki, Pedro V.; Szilveszter, Balint; Hallett, Travis; Lu, Michael T.; Puchner, Stefan B.; Simon, Tracey G.; Foldyna, Borek; Voora, Deepak; et al. (Clinical Gastroenterology and Hepatology, 2021)
Background & Aims: Hepatic steatosis has been associated with increased risk of major adverse cardiovascular events (MACE) but it is not clear whether steatosis is independently associated with risk of MACE. We investigated whether steatosis is associated with risk of MACE independently of the presence and extent of baseline coronary artery disease, assessed by comprehensive contrast-enhanced computed tomography angiography (CTA). Methods: We conducted a nested cohort study of 3756 subjects (mean age, 60.6 years; 48.4% men) who underwent coronary CTA at 193 sites in North America, from July 2010 through September 2013, as part of the PROMISE study, which included noninvasive cardiovascular analyses of symptomatic outpatients without coronary artery disease. Independent core laboratory readers measured hepatic and splenic attenuation, using non-contrast computed tomography images to identify steatosis, and evaluated coronary plaques and stenosis in coronary CTA images. We collected data on participants’ cardiovascular risk factors, presence of metabolic syndrome, and body mass index. The primary endpoint was an adjudicated composite of MACE (death, myocardial infarction, or unstable angina) during a median follow-up time of 25 months. Results: Among the 959 subjects who had steatosis (25.5% of the cohort), 42 had MACE (4.4%), whereas among the 2797 subjects without steatosis, 73 had MACE (2.6%) (hazard ratio [HR] for MACE in subjects with steatosis, 1.69; 95% CI, 1.16–2.48; P = .006 for MACE in subjects with vs without steatosis). This association remained after adjustment for atherosclerotic cardiovascular disease risk scores, significant stenosis, and metabolic syndrome (adjusted HR, 1.72; 95% CI, 1.16–2.54; P = .007) or obesity (adjusted HR, 1.75; 95% CI, 1.19–2.59; P = .005). Steatosis remained independently associated with MACE after adjustment for all CTA measures of plaques and stenosis. Conclusions: Hepatic steatosis is associated with MACE independently of other cardiovascular risk factors or extent of coronary artery disease. Strategies to reduce steatosis might reduce risk of MACE. ClinicalTrials.gov no: NCT01174550
CRIS-Team Scopus Importer:2021-06-25
Keywords: CT; Heart Disease; MAFLD; NAFLD

Association of Metabolic Phenotypes With Coronary Artery Disease and Cardiovascular Events in Patients With Stable Chest Pain - Kammerlander, Andreas A.; Mayrhofer, Thomas; Ferencik, Maros; Pagidipati, Neha J.; Karady, Julia; Ginsburg, Geoffrey S.; Lu, Michael T.; Bittner, Daniel O.; Puchner, Stefan B.; Bihlmeyer, Nathan A.; Meyersohn, Nandini M.; Emami, Hamed; et al. (Diabetes Care, 2021)
OBJECTIVE Obesity and metabolic syndrome are associated with major adverse cardiovascular events (MACE). However, whether distinct metabolic phenotypes differ in risk for coronary artery disease (CAD) and MACE is unknown. We sought to determine the association of distinct metabolic phenotypes with CAD and MACE. RESEARCH DESIGN AND METHODS We included patients from the Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE) who underwent coronary computed tomography (CT) angiography. Obesity was defined as a BMI >= 30 kg/m(2) and metabolically healthy as less than or equal to one metabolic syndrome component except diabetes, distinguishing four metabolic phenotypes: metabolically healthy/unhealthy and nonobese/obese (MHN, MHO, MUN, and MUO). Differences in severe calcification (coronary artery calcification [CAC] >= 400), severe CAD (>= 70% stenosis), high-risk plaque (HRP), and MACE were assessed using adjusted logistic and Cox regression models. RESULTS Of 4,381 patients (48.4% male, 60.5 +/- 8.1 years of age), 49.4% were metabolically healthy (30.7% MHN and 18.7% MHO) and 50.6% unhealthy (22.3% MUN and 28.4% MUO). MHO had similar coronary CT findings as compared with MHN (severe CAC/CAD and HRP; P > 0.36 for all). Among metabolically unhealthy patients, those with obesity had similar CT findings as compared with nonobese (P > 0.10 for all). However, both MUN and MUO had unfavorable CAD characteristics as compared with MHN (P <= 0.017 for all). A total of 130 events occurred during follow-up (median 26 months). Compared with MHN, MUN (hazard ratio [HR] 1.61 [95% CI 1.02-2.53]) but not MHO (HR 1.06 [0.62-1.82]) or MUO (HR 1.06 [0.66-1.72]) had higher risk for MACE. CONCLUSIONS In patients with stable chest pain, four metabolic phenotypes exhibit distinctly different CAD characteristics and risk for MACE. Individuals who are metabolically unhealthy despite not being obese were at highest risk in our cohort.
CRIS-Team WoS Importer:2021-04-09

Comparison of direct oral anticoagulants to vitamin-K antagonists as treatment for leaflet thrombosis after Transcatheter Aortic Valve Implantation (TAVI) - Ferstl, Paul; Marwan, Mohamed; Achenbach, Stephan; Bittner, Daniel (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Comparison of oral anticoagulation by vitamin-K antagonists and non-vitamin-K antagonists for treatment of leaflet thickening after transcatheter aortic valve implantation (TAVI) - Ferstl, Paul; Achenbach, Stephan; Marwan, Mohamed; Bittner, Daniel O. (International Journal of Cardiology, 2023)
Introduction: Hypoattenuated leaflet thickening (HALT), as identified by CT imaging, is not infrequent after transcatheter aortic valve implantation (TAVI). The best choice of oral anticoagulation is unknown. We compared the effectiveness of Direct Oral AntiCoagulants (DOAC) and Vitamin-K Antagonists (VKA) to resolve HALT in patients with serial CT aquisitions. Methods: A total of 46 consecutive TAVI patients in whom anticoagulation had been initiated because of HALT and who underwent follow-up CT were identified. Indication and type of anticoagulation was according to physician discretion. Patients on DOAC were compared to VKA therapy regarding resolution of HALT. Results: Mean age of the 46 patients was 80 ± 6 years (59% men), and the mean duration of anticoagulation was 156 days. Overall, 41 patients (89%) showed resolution of HALT with anticoagulation therapy, whereas HALT persisted in 5 patients (11%). Resolution of HALT was seen in 26 out of 30 (87%) patients receiving VKA and in 15 out of 16 (94%) patients receiving DOAC, respectively. Groups did not differ regarding age, cardiovascular risk factors, TAVI prosthesis type and size or duration of anticoagulation (all p > 0.05). Conclusion: Anticoagulation therapy resolves leaflet thickening after TAVI in most patients. Non-Vitamin-K antagonists seem to be an effective alternative to Vitamin-K antagonists. This finding needs to be confirmed in larger prospective trials.
CRIS-Team Scopus Importer:2023-06-09
Keywords: Anticoagulation; HALT; Leaflet thickening; TAVI

Computed tomography-derived characterisation of pericoronary,epicardial and paracardial adipose tissue and its association with myocardial ischemia as assessed by computed and invasive fractional flow - Göller, Markus; Duncker, Hendrik; Moshage, Maximilian; Dey, D.; Bittner, Daniel; Ammon, Fabian; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

CT analysis of left ventricular function predicts short term survival in patients following transcatheter aortic valve implantation: 1-year outcome data - Ijgua, Mohamed; Arnold, Martin; Eckstein, Markus; Smolka, S.; Bittner, Daniel O.; Ammon, Fabian; Kondruweit, Markus; Moshage, Maximilian; Achenbach, Susanne; Marwan, Mohamed (European Heart Journal, 2022)
CRIS-Team WoS Importer:2023-03-03

Determination of optimal fluoroscopic angulations for aorto-coronary ostial interventions from coronary computed tomography angiography - Hell, Michaela; Schlundt, Christian; Bittner, Daniel O.; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2020)
Background: An optimal aorto-coronary angiographic projection, characterized by an orthogonal visualization of the proximal coronary artery, is crucial for interventional success. We determined the distribution of optimal C-arm positions and assessed their feasibility by invasive coronary angiography. Methods: Orthogonal aorto-coronary ostial angulations were determined in 310 CT data sets. In 100 patients undergoing subsequent invasive angiography, we assessed if the CT-predicted angulations were achievable by the C-arm system. If the predicted projection was not achievable due to mechanical constraints of the C-arm system, the most close, achievable angulation was determined. Patient characteristics were analyzed regarding the distribution of optimal angulations and its feasibility by the C-arm system. Results: For the left ostium, CT revealed a mean angulation of LAO 23 ​± ​21°/cranial 25 ​± ​23° (90% of patients with a LAO/cranial angulation, 3% LAO/caudal, 4% RAO/cranial, 3% RAO/caudal) and were achievable by the C-arm system in 87% of patients. For the right ostium, the mean CT-predicted orthogonal angulation was LAO 36 ​± ​37°/cranial 36 ​± ​51° (84% LAO/cranial, 2% LAO/caudal, 14% RAO/caudal) and achievable by the C-arm system in 45% of patients. For the left ostium, a higher body weight was associated with a steeper LAO/cranial angulation being less feasible by the C-arm system due to mechanical constraints. Conclusions: Orthogonal aorto-left coronary angulations show a relative narrow distribution predominately in LAO/cranial position whereas a wider range of angulations was found for the right coronary ostium. The feasibility of CT-predicted angulations by the C-arm system is more restricted for the right than the left coronary ostium.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Angulation; Computed tomography angiography; Coronary intervention; Ostial lesion

Differences of inflammatory cytokine profile in patients with vulnerable plaque: A coronary CTA study - Roesner, Caroline; Göller, Markus; Raaz-Schrauder, Dorette; Dey, Damini; Kilian, Tobias; Achenbach, Stephan; Marwan, Mohamed; Bittner, Daniel O. (Atherosclerosis, 2022)
Background and aims: Various pro-and anti-inflammatory biomarkers are involved in the process of atherosclerosis. We analyzed the association of different biomarkers with coronary plaque volume and vulnerable plaque subcomponents. Methods: In 301 patients undergoing coronary CT angiography (CTA), total coronary plaque volume (TPV) and subcomponents including non-calcified plaque volume (NCPV) and vulnerable plaque burden were quantified using semi-automated software. Serum was analyzed for various cytokines. Results: Out of 301 patients, 207 (69%) were male. The mean age was 59 +/- 10 years. Patients were divided using the median of TPV, NCPV and vulnerable plaque burden. In univariable analysis, patients with high TPV, high NCPV and high vulnerable plaque burden showed significant higher serum levels for IFN?, IL-1a,-2,-4,-10 and-17 and significant lower levels for IL-8 and MCP-1 (all p < 0.05). Multivariable analysis showed positive associations between high vulnerable plaque burden, IL-1a (OR 2.60, p = 0.001) and Eotaxin (OR 1.89, p = 0.020), and inverse association to MCP-1 (OR 0.33, p < 0.001), independent of age, gender and CVRF. In exploratory subanalyses, patients with presence of atherosclerosis (n = 247; 82%) showed significantly higher levels of IL-17 in all subgroups with high vulnerable plaque burden, irrespective of overall plaque volume (all p < 0.001). Conclusions: The cytokine profile significantly differs between patients with high and low coronary plaque volume. IL-1a and IL-17 seem to play a major proatherogenic role in vulnerable plaque formation, whereas MCP-1 paradoxically portends protective effects. Longitudinal studies with serial cytokine testing are needed to identify potential targets for therapeutic interventions.
CRIS-Team WoS Importer:2022-06-24
Keywords: Inflammatory biomarkers; Interleukin; Atherosclerosis; Coronary CT-angiography; Plaque volume; Vulnerable plaque

Independent predictors of major cardiovascular events as quantitatively assessed by coronary CT-angiography: a long-term follow-up analysis - Bittner, Daniel O.; Roesner, C.; Kilian, Tobias; Göller, Markus; Dey, D.; Raaz-Schrauder, Dorette; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Influence of gender on coronary atherosclerosis and inflammatory biomarker profile: a CT angiographic study - Bittner, Daniel O.; Rösner, Caroline; Göller, Markus; Raaz-Schrauder, Dorette; Dey, D.; Kilian, Tobias; Achenbach, Susanne; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Influence of lesion location on the accuracy of CT derived FFR: head-to-head comparison with invasive FFR - Moshage, Maximilian; Smolka, S.; Achenbach, Stephan; Ammon, Fabian; Ferstl, Paul; Göller, Markus; Bittner, Daniel O.; Uehlein, Sabrina; Bal, Zeynep; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Influence of reconstruction kernels on the accuracy of CT-derived fractional flow reserve - Ammon, Fabian; Moshage, Maximilian; Smolka, Silvia; Göller, Markus; Bittner, Daniel O.; Achenbach, Stephan; Marwan, Mohamed (European Radiology, 2021)
Objectives: We evaluated the influence of image reconstruction kernels on the diagnostic accuracy of CT-derived fractional flow reserve (FFRCT) compared to invasive FFR in patients with coronary artery disease. Methods: Sixty-nine patients, in whom coronary CT angiography was performed and who were further referred for invasive coronary angiography with FFR measurement via pressure wire, were retrospectively included. CT data sets were acquired using a third-generation dual-source CT system and rendered with medium smooth (Bv40) and sharp (Bv49) reconstruction kernels. FFRCT was calculated on-site using prototype software. Coronary stenoses with invasive FFR ≤ 0.80 were classified as significant. Agreement between FFRCT and invasive FFR was determined for both reconstruction kernels. Results: One hundred analyzed vessels in 69 patients were included. Twenty-five vessels were significantly stenosed according to invasive FFR. Using a sharp reconstruction kernel for FFRCT resulted in a significantly higher correlation with invasive FFR (r = 0.74, p < 0.01 vs. r = 0.58, p < 0.01; p = 0.04) and a higher AUC in ROC curve analysis to correctly identify/exclude significant stenosis (AUC = 0.92 vs. AUC = 0.82 for sharp vs. medium smooth kernel, respectively, p = 0.02). A FFRCT value of ≤ 0.8 using a sharp reconstruction kernel showed a sensitivity of 88% and a specificity of 92% for detecting ischemia-causing lesions, resulting in a diagnostic accuracy of 91%. The medium smooth reconstruction kernel performed worse (sensitivity 60%, specificity 89%, accuracy 82%). Conclusion: Compared to invasively measured FFR, FFRCT using a sharp image reconstruction kernel shows higher diagnostic accuracy for detecting lesions causing ischemia, potentially altering decision-making in a clinical setting. Key Points: • Image reconstruction parameters influence the diagnostic accuracy of simulated fractional flow reserve derived from coronary computed tomography angiography. • Using a sharp kernel image reconstruction algorithm delivers higher diagnostic accuracy compared to medium smooth kernel image reconstruction (gold standard invasive fractional flow reserve).
CRIS-Team Scopus Importer:2021-11-12
Keywords: Computed tomography angiography; Coronary artery disease; Fractional flow reserve; myocardial; Image processing; computer-assisted

Lipoprotein subclasses are associated with Hepatic steatosis: insights from the prospective multicenter imaging study for the evaluation of chest pain (PROMISE) clinical trial - Karady, Julia; McGarrah, Robert W.; Nguyen, Maggie; Giamberardino, Stephanie N.; Meyersohn, Nandini; Lu, Michael T.; Staziaki, Pedro V.; Puchner, Stefan B.; Bittner, Daniel O.; Foldyna, Borek; Mayrhofer, Thomas; Connelly, Margery A.; et al. (American Journal of Preventive Cardiology, 2024)
Objectives: To determine the relationship between lipoprotein particle size/number with hepatic steatosis (HS), given its association with traditional lipoproteins and coronary atherosclerosis. Methods: Individuals with available CT data and blood samples enrolled in the PROMISE trial were studied. HS was defined based on CT attenuation. Lipoprotein particle size/number were measured by nuclear magnetic resonance spectroscopy. Principal components analysis (PCA) was used for dimensionality reduction. The association of PCA factors and individual lipoprotein particle size/number with HS were assessed in multivariable regression models. Associations were validated in an independent cohort of 59 individuals with histopathology defined HS. Results: Individuals with HS (n=410/1,509) vs those without (n=1,099/1,509), were younger (59±8 vs 61±8 years) and less often females (47.6 % vs 55.9 %). All PCA factors were associated with HS: factor 1 (OR:1.36, 95 %CI:1.21–1.53), factor 3 (OR:1.75, 95 %CI:1.53–2.02) and factor 4 (OR:1.49; 95 %CI:1.32–1.68) were weighted heavily with small low density lipoprotein (LDL) and triglyceride-rich (TRL) particles, while factor 2 (OR:0.86, 95 %CI:0.77–0.97) and factor 5 (OR:0.74, 95 %CI:0.65–0.84) were heavily loaded with high density lipoprotein (HDL) and larger LDL particles. These observations were confirmed with the analysis of individual lipoprotein particles in PROMISE. In the validation cohort, association between HS and large TRL (OR: 8.16, 95 %CI:1.82–61.98), and mean sizes of TRL- (OR: 2.82, 95 %CI:1.14–9.29) and HDL (OR:0.35, 95 %CI:0.13–0.72) were confirmed. Conclusions: Large TRL, mean sizes of TRL-, and HDL were associated with radiographic and histopathologic HS. The use of lipoprotein particle size/number could improve cardiovascular risk assessment in HS.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Cardiac CT; Hepatic steatosis; Lipoprotein; Lipoprotein particles; Lipoprotein subclasses

Pericoronary adipose tissue CT attenuation and its association with serum levels of atherosclerosis-relevant inflammatory mediators, coronary calcification and major adverse cardiac events - Göller, Markus; Achenbach, Stephan; Herrmann, Nicolai; Bittner, Daniel O.; Kilian, Tobias; Dey, Damini; Raaz-Schrauder, Dorette; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2021)
Background: Increased attenuation of pericoronary adipose tissue (PCAT) around the right coronary artery (RCA) derived from coronary CTA might detect coronary inflammation. We investigated a potential association between RCA PCAT attenuation and serum levels of atherosclerosis-relevant cytokines and MACE (coronary revascularization, myocardial infarction and/or cardiac death). Methods: Blood samples of 293 clinically stable individuals (59.0 ​± ​9.8 years, 69% males) were analyzed for atherosclerosis-relevant cytokines including interleukin (IL)-2, IL- 4, IL-6, IL-7, IL-8, IL-10, IL-13, IL-15, IL-17, TNF-a, IP-10, CRP, MCP-1, MIP-1a, Eotaxin and GM-CSF. Subjects also underwent coronary calcium scoring (CCS) followed by CTA. PCAT CT attenuation was measured around the RCA using semi-automated software. Increased RCA PCAT attenuation was defined as PCAT attenuation above the 75th percentile (>−73.5 HU). To assess MACE, 232 individuals were followed for a mean duration of 9.6 ​± ​2.1 years. Results: In patients with increased RCA PCAT attenuation the serum levels of MCP-1 were increased (p ​< ​0.01), whereas levels of anti-inflammatory mediators IL-4 and -13 were significantly reduced (each p ​< ​0.05). Adipocytokine MCP-1 (r ​= ​0.23, p ​< ​0.01) and pro-inflammatory mediator IL-7 (r ​= ​0.12, p ​= ​0.04) showed a mild positive correlation with RCA PCAT attenuation, whereas anti-inflammatory mediators Il-4, -10 and -13 correlated inversely (each r < −0.12, each p ​< ​0.05). 40/232 patients experienced MACE during follow-up. In multivariable Cox regression analysis increased RCA PCAT attenuation was shown to be an independent predictor of MACE (HR 2.01, p ​= ​0.044). Conclusions: Increased RCA PCAT CT attenuation shows a weak association with serum levels of selected atherosclerosis-relevant inflammatory biomarkers. Increased RCA PCAT attenuation is an independent predictor of MACE and may potentially guide future prevention strategies in stable patients.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Atherosclerosis-relevant inflammatory biomarkers; Coronary calcium score; CT attenuation; Inflammation; MACE; Pericoronary adipose tissue

Resolution of leaflet thrombosis under anticoagulant therapy in patients after transcatheter aortic valve implantation: influence of prosthesis type and size - Ferstl, Paul; Arnold, Martin; Göller, Markus; Ammon, Fabian; Smolka, S.; Moshage, Maximilian; Uehlein, Sabrina; Achenbach, Stephan; Bittner, Daniel O.; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Risk factors for cardiovascular disease among individuals with hepatic steatosis - Karady, Julia; Ferencik, Maros; Mayrhofer, Thomas; Meyersohn, Nandini M.; Bittner, Daniel O.; Staziaki, Pedro; Szilveszter, Balint; Hallett, Travis R.; Lu, Michael T.; Puchner, Stefan B.; Simon, Tracey G.; Foldyna, Borek; et al. (Hepatology Communications, 2022)
Cardiovascular disease (CVD) is the leading cause of mortality in adults with hepatic steatosis (HS). However, risk factors for CVD in HS are unknown. We aimed to identify factors associated with coronary artery disease (CAD) and incident major adverse cardiovascular events (MACE) in individuals with HS. We performed a nested cohort study of adults with HS detected on coronary computed tomography in the PROspective Multicenter Imaging Study for Evaluation of chest pain (PROMISE) trial. Obstructive CAD was defined as ≥50% coronary stenosis. MACE included hospitalization for unstable angina, nonfatal myocardial infarction, or all-cause death. Multivariate modeling, adjusted for age, sex, atherosclerotic CVD (ASCVD) risk score and body mass index, identified factors associated with obstructive CAD. Cox regression, adjusted for ASCVD risk score, determined the predictors of MACE. A total of 959 of 3,756 (mean age 59.4 years, 55.0% men) had HS. Obstructive CAD was present in 15.2% (145 of 959). Male sex (adjusted odds ratio [aOR] = 1.83, 95% confidence interval [CI] 1.18–1.2.84; p = 0.007), ASCVD risk score (aOR = 1.05, 95% CI 1.03–1.07; p < 0.001), and n-terminal pro-b-type natriuretic peptide (NT-proBNP; aOR = 1.90, 95% CI 1.38–2.62; p < 0.001) were independently associated with obstructive CAD. In the 25-months median follow-up, MACE occurred in 4.4% (42 of 959). Sedentary lifestyle (adjusted hazard ratio [aHR] = 2.53, 95% CI 1.27–5.03; p = 0.008) and NT-proBNP (aOR = 1.50, 95% CI 1.01–2.25; p = 0.046) independently predicted MACE. Furthermore, the risk of MACE increased by 3% for every 1% increase in ASCVD risk score (aHR = 1.03, 95% CI 1.01–1.05; p = 0.02). Conclusion: In individuals with HS, male sex, NT-pro-BNP, and ASCVD risk score are associated with obstructive CAD. Furthermore, ASCVD, NT-proBNP, and sedentary lifestyle are independent predictors of MACE. These factors, with further validation, may help risk-stratify adults with HS for incident CAD and MACE.
CRIS-Team Scopus Importer:2022-11-04

Risk Stratification With the Use of Coronary Computed Tomographic Angiography in Patients With Nonobstructive Coronary Artery Disease - Taron, Jana; Foldyna, Borek; Mayrhofer, Thomas; Osborne, Michael T.; Meyersohn, Nandini; Bittner, Daniel O.; Puchner, Stefan B.; Emami, Hamed; Lu, Michael T.; Ferencik, Maros; Pagidipati, Neha J.; Douglas, Pamela S.; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2021)
Objectives: The purpose of this study was to develop a risk prediction model for patients with nonobstructive CAD. Background: Among stable chest pain patients, most cardiovascular (CV) events occur in those with nonobstructive coronary artery disease (CAD). Thus, developing tailored risk prediction approaches in this group of patients, including CV risk factors and CAD characteristics, is needed. Methods: In Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE) computed tomographic angiography patients, a core laboratory assessed prevalence of CAD (nonobstructive 1% to 49% left main or 1% to 69% stenosis any coronary artery), degree of stenosis (minimal: 1% to 29%; mild: 30% to 49%; or moderate: 50% to 69%), high-risk plaque (HRP) features (positive remodeling, low-attenuation plaque, and napkin-ring sign), segment involvement score (SIS), and coronary artery calcium (CAC). The primary end point was an adjudicated composite of unstable angina pectoris, nonfatal myocardial infarction, and death. Cox regression analysis determined independent predictors in nonobstructive CAD. Results: Of 2,890 patients (age 61.7 years, 46% women) with any CAD, 90.4% (n = 2,614) had nonobstructive CAD (mean age 61.6 yrs, 46% women, atherosclerotic cardiovascular disease [ASCVD] risk 16.2%). Composite events were independently predicted by ASCVD risk (hazard ratio [HR]: 1.03; p = 0.001), degree of stenosis (30% to 69%; HR: 1.91; p = 0.011), and presence of ≥2 HRP features (HR: 2.40; p = 0.008). Addition of ≥2 HRP features to: 1) ASCVD and CAC; 2) ASCVD and SIS; or 3) ASCVD and degree of stenosis resulted in a statistically significant improvement in model fit (p = 0.0036; p = 0.0176; and p = 0.0318; respectively). Patients with ASCVD ≥7.5%, any HRP, and mild/moderate stenosis had significantly higher event rates than those who did not meet those criteria (3.0% vs. 6.2%; p = 0.007). Conclusions: Advanced coronary plaque features have incremental value over total plaque burden for the discrimination of clinical events in low-risk stable chest pain patients with nonobstructive CAD. This may be a first step to improve prevention in this cohort with the highest absolute risk for CV events.
CRIS-Team Scopus Importer:2021-05-14
Keywords: computed tomographic angiography; nonobstructive coronary artery disease; risk stratification

Small whole heart volume predicts cardiovascular events in patients with stable chest pain: insights from the PROMISE trial - Foldyna, Borek; Zeleznik, Roman; Eslami, Parastou; Mayrhofer, Thomas; Scholtz, Jan Erik; Bittner, Daniel O.; Bittner, Daniel O.; Meyersohn, Nandini M.; Puchner, Stefan B.; Emami, Hamed; Pellikka, Patricia A.; Aerts, Hugo J.W.L.; et al. (European Radiology, 2021)
Objectives: The size of the heart may predict major cardiovascular events (MACE) in patients with stable chest pain. We aimed to evaluate the prognostic value of 3D whole heart volume (WHV) derived from non-contrast cardiac computed tomography (CT). Methods: Among participants randomized to the CT arm of the Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE), we used deep learning to extract WHV, defined as the volume of the pericardial sac. We compared the WHV across categories of cardiovascular risk factors and coronary artery disease (CAD) characteristics and determined the association of WHV with MACE (all-cause death, myocardial infarction, unstable angina; median follow-up: 26 months). Results: In the 3798 included patients (60.5 ± 8.2 years; 51.5% women), the WHV was 351.9 ± 57.6 cm3/m2. We found smaller WHV in no- or non-obstructive CAD, women, people with diabetes, sedentary lifestyle, and metabolic syndrome. Larger WHV was found in obstructive CAD, men, and increased atherosclerosis cardiovascular disease (ASCVD) risk score (p < 0.05). In a time-to-event analysis, small WHV was associated with over 4.4-fold risk of MACE (HR (per one standard deviation) = 0.221; 95% CI: 0.068–0.721; p = 0.012) independent of ASCVD risk score and CT-derived CAD characteristics. In patients with non-obstructive CAD, but not in those with no- or obstructive CAD, WHV increased the discriminatory capacity of ASCVD and CT-derived CAD characteristics significantly. Conclusions: Small WHV may represent a novel imaging marker of MACE in stable chest pain. In particular, WHV may improve risk stratification in patients with non-obstructive CAD, a cohort with an unmet need for better risk stratification. Key Points: • Heart volume is easily assessable from non-contrast cardiac computed tomography. • Small heart volume may be an imaging marker of major adverse cardiac events independent and incremental to traditional cardiovascular risk factors and established CT measures of CAD. • Heart volume may improve cardiovascular risk stratification in patients with non-obstructive CAD.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Cardiac volume; Coronary disease; Heart failure; Multidetector computed tomography

The association of pericoronary adipose tissue attenuation with major adverse cardiac events (MACE) and atherosclerosis-relevant inflammatory mediators - Göller, Markus; Achenbach, Stephan; Herrmann, N.; Bittner, Daniel O.; Ammon, Fabian; Kilian, Tobias; Smolka, S.; Uehlein, Sabrina; Moshage, Maximilian; Raaz-Schrauder, Dorette; Dey, D.; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12